Correlation between coping strategies and health status of burn patients after discharge at burn centers in Tehran - Safavi Bayat, Z; Ghasemi, M; Mohtashami, J; Naderiravesh, N; Akbarzadeh Baghban, A. R. (Advances in Nursing & Midwifery, 2010)
Background and aim Burn is the third leading cause of death leading to decreased quality of life and disability. Deformity and dysfunction in afflicted patients make their return to community hard. They often apply inappropriate coping strategies, resulting in incompliance with the disease, lack of seeking assistance and impairment of health condition. This descriptive-correlational study was conducted to identify the correlation between coping strategies and health condition of burned patients after discharge at burn centers of Tehran in 2009. Materials and methods 89 patients experiencing moderate to severe burns over the age of 15 after at least 1 month or at most 5 years were selected with convenience sampling method. 3 questionnaires including “Personal Characteristics,” “Burn Specific Health Status Scale” and “Coping with Burn” were used for data collection. After identifying content and face validities of the questionnaires, their reliabilities were identified by internal consistency. Data were gathered by self-report and medical records of patients and also were analyzed by SPSS 14. Findings Most subjects (%41.6) had moderate health status. None had very good health status. Physical domain (%44) was better than other aspects. Psychological (%40.2) and socioeconomic (%39.3) domains were in the second and third ranks. In addition, most subjects (%56.8) had used avoidance coping strategy after discharge while least of them (%51) had used emotionally-focused strategy. A correlation was found between health status and coping strategy. Those using avoidance had weaker heath condition than others with a statistical significance in psychological domain (P=0.01). Conclusion Findings showed that the subjects had better status in physical domain than socioeconomic one. Most of them had used avoidance strategy and health status was correlated with coping strategies. Keywords: Coping strategies, Health status, Discharge, Burn patient. *Corresponding Author: Lecturer, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. E-mail: zahrasb16@yahoo.com